Gerakan Sosial pada Elite Desa dalam Penjualan Tanah Negara - Rifqi, Abdulloh Moh; Abdurrahman Marzuki; Muhammad Mukhobbir Risalah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study examines agrarian conflict in Kedamean Village related to the sale of state-owned land by the village government, which has triggered a peasant movement aimed at maintaining access to agricultural land. The state-owned land plays an important role as the economic foundation of a community that depends on the agricultural sector; however, it is threatened by a planned housing development project by PT. Prima Damai Permai, despite the unclear legal status of land ownership. The objective of this study is to analyze the peasant movement organized under AMPTN in defending state-owned land and to identify the strategies employed in responding to village government policies. This research uses a qualitative method with a case study approach, employing observation, interviews, and documentation techniques. The findings show that AMPTN represents a collective peasant movement focused on rejecting the allegedly non-transparent process of selling state-owned land and pushing for legal action against parties involved in the village administration. The movement has also succeeded in building support networks with non-governmental organizations, mass media, and regional legislative institutions such as the Gresik Regency DPRD, as part of its strategy to strengthen bargaining power in the agrarian conflict. In conclusion, the AMPTN movement reflects a form of social resistance by rural communities in maintaining access to agrarian resources that are vital for their livelihood sustainability. Limited financial resources have influenced the movement’s strategy, leading mobilization to rely more on social solidarity and external network support rather than formal legal assistance such as lawyers. Keywords: Agrarian Conflict, Elites, Peasant Movement, Sale Of State-Owned Land.